Use of Pavlik Harness in the Treatment of Infantile Femur Fracture: Clinical and Radiological Outcome (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Infantile femur fractures are a significant clinical challenge, with treatment modalities varying widely. The Pavlik Harness, traditionally used for developmental dysplasia of the hip, has been employed in the conservative management of femur fractures in infants with promising outcomes. This study aims to evaluate the clinical and radiological outcomes of using the Pavlik Harness in the treatment of femur fractures in infants aged less than 6 months. Methods: This retrospective observational study was conducted at ChattogramMaa-O-Shishu Hospital Medical College in Bangladesh from January 2021 to December 2023, encompassing a review of 22 cases of isolated femur fractures in infants treated with the Pavlik Harness. Inclusion criteria were age under 6 months, isolated femur fracture, and fracture involving the proximal and middle third of the femur. Exclusion criteria included polytrauma, neuromuscular disease, and incomplete medical records or lack of parental consent. Result: The majority of fractures were due to birth trauma (81.82%), with a higher incidence in males (63.64%) and right-sided fractures (63.64%). The mean age and weight at the time of injury were 11.00±20.07 days and 2.86±0.52 kg, respectively. Initial angulation was 17.91±2.67 degrees AP/Vulgus and 14.82±3.34 degrees Lateral/Procurvatum. At the 2-month follow-up, significant improvements were observed with mean angulations of 8.09±2.94 degrees AP/Vulgus and 5.91±1.80 degrees Lateral/Procurvatum. Limb length discrepancy was minimal, with a mean of 2.32±0.39 cm. The treatment was associated with a low complication rate, with only 9.09% of cases developing skin excoriation. Conclusion: The Pavlik Harness is an effective conservative treatment for infantile femur fractures, ensuring satisfactory clinical and radiological outcomes. The harness facilitates proper fracture alignment and promotes favorable bone healing dynamics, with minimal limb length discrepancy and low complication rates. These findings support the continued use of the Pavlik Harness in appropriate cases and underscore the need for further prospective studies to validate these results.Journal of Paediatric Surgeons of Bangladesh (2023) Vol. 14 (1 & 2): 17-23